On Cuba, diplomats, ultrasound, and intermodulation distortion. (January 2019) - Yan, Chen; Fu, Kevin; Xu, Wenyuan
Abstract: This paper analyzes how ultrasounds could have unintentionally led to the AP news recordings of metallic sounds heard by diplomats in Cuba. Beginning with screen shots of the acoustic spectral plots from the AP news, we reverse engineered ultrasonic signals that could lead to those outcomes as a result of intermodulation distortion with non-linearity in the acoustic transmission medium. We created a proof of concept ultrasonic device that amplitude modulates a signal over an inaudible ultrasonic carrier. When a second inaudible ultrasonic source interfered with the primary source, intermodulation distortion created audible byproducts that share spectral characteristics with audio from the AP news. Our conclusion is that if ultrasound played a role in harming diplomats in Cuba, then a plausible cause is intermodulation distortion between ultrasonic signals that unintentionally synthesize audible tones. In other words, acoustic interference without malicious intent to cause harm could have led to the audible sensations in Cuba. Highlights: We show how ultrasounds and intermodulation distortion could explain the reported symptoms and the audio recording in Cuba. We theoretically discussed the mechanism of generating a spectral plot similar to the one from the AP news via simulation. We experimentally validated that ultrasounds from multiple parties could have collided to produce audible byproducts.